A comparative discourse analysis of hedges in opinion-giving by Arab EFL and Malay ESL learners in WhatsApp focused group discussions - Alkhawaja, Hussein Walid Hussein; Paramasivam, Shamala (2015)
Communicating appropriately in a target language (English language) requires both ESL Malaysian learners and their counterparts Arab EFL learners to develop linguistic and pragmatic awareness in the target language. One aspect of such development is their use of linguistic hedges to modify their speech acts and realize politeness. However, little attention has been given to investigate these learners’ linguistic and pragmatic use of these devices. The purpose of this study is to fill this gap in the literature by conducting a study that examines the use of hedges in relation to politeness between these two groups of learners while exchanging their opinions in focused group discussions created on WhatsApp application. To this end, the current study used a descriptive design that employed quantitative and qualitative methods to identify the types, frequency, and pragmatic functions of hedges in relation to politeness. The sample consisted of four EFL Arab learners and five Malaysian ESL learners who study English in a Malaysian university. The data collected in forms of comments by means of focused group discussions were coded and analyzed based on Fraser’s (2010) Taxonomy of English Hedges. They were then uploaded to Excel to find the frequency and percentages of the types of hedges used. This was followed by a detailed pragmatic analysis based on Brown and Levinson’s (1987) Politeness Theory. The findings showed that both types of learners use hedges in stating their opinions. However, they use different categories and hedges types and realize politeness differently.